2017
DOI: 10.1002/etc.3739
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effects on wood frogs chronically exposed to environmentally relevant concentrations of two neonicotinoid insecticides

Abstract: Neonicotinoids are prophylactically used globally on a variety of crops, and there is concern for the potential impacts of neonicotinoids on aquatic ecosystems. The intensive use of pesticides on crops has been identified as a contributor to population declines of amphibians, but currently little is known regarding the sublethal effects of chronic neonicotinoid exposure on amphibians. The objective of the present study was to characterize the sublethal effect(s) of exposure to 3 environmentally relevant concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
3
9

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 57 publications
5
49
3
9
Order By: Relevance
“…This is likely attributable to spray drift from nearby agricultural activities, but even at the St. Denis National Wildlife Area there is prescribed use of herbicides to control alien plant species (Environment Canada ). However, we found little evidence for negative effects of the most commonly detected pesticides here, namely 2,4‐D, MCPA, and imidacloprid (Relyea ; Johnasson et al ; Robinson et al ; Lee‐Jenkins and Robinson ). Without detailed, field‐based investigation into the single and combined effects of chronic agrochemical exposure to wood frogs, we caution that these results are preliminary and correlative.…”
Section: Discussionmentioning
confidence: 57%
“…This is likely attributable to spray drift from nearby agricultural activities, but even at the St. Denis National Wildlife Area there is prescribed use of herbicides to control alien plant species (Environment Canada ). However, we found little evidence for negative effects of the most commonly detected pesticides here, namely 2,4‐D, MCPA, and imidacloprid (Relyea ; Johnasson et al ; Robinson et al ; Lee‐Jenkins and Robinson ). Without detailed, field‐based investigation into the single and combined effects of chronic agrochemical exposure to wood frogs, we caution that these results are preliminary and correlative.…”
Section: Discussionmentioning
confidence: 57%
“…The frogs had been exposed to environmentally relevant concentrations (1, 10, and 100 mg/L) of imidacloprid (Admire [240 g/L of imidacloprid; Bayer CropScience; CAS no. Measured concentrations generally increased throughout the 6-wk exposure period; however, for simplicity we present the results using nominal concentrations (Robinson et al 2017; also see the Supplemental Data, Table S1). 153719-23-4]) from Gosner stages 25 to 27 to Gosner stage 46 (Gosner 1960) in outdoor mesocosms (Robinson et al 2017).…”
Section: Amphibian Husbandrymentioning
confidence: 99%
“…Most of these studies have been acute lethality experiments in which exposure and effect concentrations (range in mg/L; Gibbons et al 2014) exceeded environmentally relevant concentrations (range from ng/L up to 320 mg/L; Anderson et al 2013;Main et al 2014Main et al , 2016Morrissey et al 2015;Smalling et al 2015;Struger et al 2017). Previous work conducted in our laboratory using outdoor mesocosms found that wood frog tadpoles (Lithobates sylvaticus) chronically exposed throughout development to environmentally relevant concentrations of imidacloprid or thiamethoxam had increased survival and a minor delay in completing metamorphosis compared with controls (Robinson et al 2017). Previous work conducted in our laboratory using outdoor mesocosms found that wood frog tadpoles (Lithobates sylvaticus) chronically exposed throughout development to environmentally relevant concentrations of imidacloprid or thiamethoxam had increased survival and a minor delay in completing metamorphosis compared with controls (Robinson et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…, Sawatzky , Robinson et al. ). This work was conducted by Laboratory Services at Environment Canada's National Wildlife Research Centre.…”
Section: Methodsmentioning
confidence: 99%